Ultra-bright green-emitting phosphors with an internal quantum efficiency of over 90% for high-quality WLEDs. Issue 12 (5th March 2021) - Li, Yanyan; Yin, Yuan; Wang, Tianli; Wu, Junxiao; Zhang, Jia; Yu, Shuaishuai; Zhang, Meiguang; Zhao, Lei; Wang, Wenjie
Abstract : Ultra-bright color-tunable phosphors of the form CaAl4 O7 :0.04Ce, z Tb with high quantum efficiency were synthesized. Abstract : There is an urgent need to develop phosphors with high quantum efficiencies (QEs) since white light-emitting diodes (WLEDs) have emerged as a new generation of illumination materials. Utilizing energy transfer to improve the absorption of activators and adjust the emission colors of samples is one effective strategy. Here, color-tunable phosphors of the form CaAl4 O7 :Ce, Tb were synthesized aiming at efficient energy transfer from Ce 3+ to Tb 3+ . Since Tb 3+ can be suitably sensitized by Ce 3+, the co-doped phosphors can be effectively excited by near-ultraviolet (NUV) light. The internal QE of CaAl4 O7 :0.04Ce, 0.04Tb under 350 nm excitation is as high as 92.55%, and the external QE is 71.02%. A WLED fabricated from BAM:Eu 2+, CaAl4 O7 :0.04Ce, 0.04Tb, and CaAlSiN3 :Eu 2+ with a 365 nm LED chip exhibited a correlated color temperature (CCT) of 4706 K and a color rendering index (CRI, R a ) of 81.44. The energy transfer mechanism and thermal stability of the phosphor were also investigated. The results provide an effective approach for developing highly efficient green-emitting phosphors for NUV WLEDs.